Benchmarking Transaction and Analytical Processing Systems The Creation of a Mixed Workload Benchmark and its Application - Bog, Anja.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Systems for Online Transaction Processing (OLTP) and Online Analytical Processing (OLAP) are currently separate. The potential of the latest technologies and changes in operational and analytical applications over the last decade have given rise to the unification of these systems, which can be of benefit for both workloads. Research and industry have reacted and prototypes of hybrid database systems are now appearing. Benchmarks are the standard method for evaluating, comparing and supporting the development of new database systems. Because of the separation of OLTP and OLAP systems, existing benchmarks are only focused on one or the other. With the rise of hybrid database systems, benchmarks to assess these systems will be needed as well. Based on the examination of existing benchmarks, a new benchmark for hybrid database systems is introduced in this book. It is furthermore used to determine the effect of adding OLAP to an OLTP workload and is applied to analyze the impact of typically used optimizations in the historically separate OLTP and OLAP domains in mixed-workload scenarios.
Introduction -- Part I: Background of Transactional and Analytical Systems in Logical Database Design and Benchmarking -- Part II: Towards a Benchmark for Mixed Workloads and its Application in Evaluating Database Schemas -- Part III: Implementation, Evaluation, and Discussion -- Part IV: Appendix.
Keywords: Business; Information technology; Business -- Data processing; Computer system failures; Computers; Database management; Computer simulation; Business and Management; IT in Business; Database Management; Models and Principles; System Performance and Evaluation; Simulation and Modeling